Clean Water Management Using Used Pots to Meet Clean Water Needs in Garantung Village, Maliku District, Pulang Pisau Regency - Tarita Aprilani Sitinjak (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Garantung village in Maliku, Pulang Pisau, Palangka Raya is a village with peat land. The water contain high Ferrum (Fe) and Manganese (Mn), smelly and brown water, as an inflict the lack of clean water on village. Based on the problem mention, these community service by Palangka Raya University held. The water treatment activity held by apply a simple filtration system. The purpose of this community service is to help the villager, obtain clean water with simple and cheap method, using used pot, gravel, sand, flannel, and tissue. The water treatment activities start with the socialization about clean water and it’s containments, following with training. The result show that after simple water treatment applied the water color significantly change, so it is can be used to washing clothes and raw foods. In order to achieve the real clean wate it is needed another water treatment activities.